A novel self‐expanding transcatheter heart valve: Shaping the story beyond accuracy. Issue 6 (18th November 2019) - Seth, Ashok; Kumar, Vijay
Key Points: As transcatheter aortic valve implantation expands to low risk patients, the key to prolonged survival would be large effective orifice area with extremely low rates of paravalvular leak and permanent pacemaker implantation. New transcatheter valve technologies look promising to enable this, ACURATE neo is one such device. The results of ongoing trials with ACURATE neo and ACURATE neo2 are keenly awaited.